Intermittent Fasting: Weighing the Benefits and Drawbacks for Health and Longevity – A Comprehensive Literature Review - Wojtczak, Marta; Michał Pniak; Paweł Miklis; Maciej Mawlichanów; Aleksandra Ciesielska; Aleksandra Sieradzka; Krzysztof Szerej; Alicja Kot; Natalia Myśliwiec; Adrian Różycki (Quality in Sport, 2025)
Introduction: Obesity rates have risen sharply in recent decades, with one in eight people worldwide living with obesity in 2022. This has driven interest in the search for effective and sustainable dietary strategies. Intermittent fasting (IF), which alternates periods of eating and fasting, has gained considerable attention as a tool for weight management and overall health improvement. Unlike traditional calorie-restricted diets, IF’s simplicity and flexibility make it more accessible, potentially increasing adherence and long-term sustainability. Purpose: This study reviews current knowledge on IF, evaluating its physiological mechanisms, health benefits, risks, and long-term implications. It focuses on weight management, glucose metabolism, cardiovascular health, cognitive function, circadian rhythm, and sports performance, while addressing challenges related to safety and sustainability. Materials and Methods: This study reviews existing literature, including clinical trials, meta-analyses, and observational studies. It compares IF protocols such as alternate-day fasting (ADF), the 5:2 diet, and time-restricted eating (TRE), emphasizing physiological effects and practical implications. Conclusion: Intermittent fasting represents a promising dietary intervention with wide-ranging health benefits, from weight management to improved metabolic and cognitive health. However, challenges such as nutritional deficiencies, risks of hypoglycemia, and limited long-term data highlight the need for personalized approaches and further investigation. Future research should prioritize large-scale, long-term studies to refine fasting protocols and ensure safety and effectiveness across diverse populations. By addressing these gaps, IF could evolve into a sustainable, evidence-based strategy for improving global health outcomes.